1980
DOI: 10.1002/ijc.2910260522
|View full text |Cite
|
Sign up to set email alerts
|

The effect of bursectomy on the adoptive transfer of resistance to Marek's disease

Abstract: Immunization with inactivated viral antigens protected chickens against Marek's disease. Non-immunized chickens could be protected by injections of spleen cells but not of serum from immunized, histocompatible donors. Chickens rendered agamma-globulinaemic by bursectomy and irradiation could also be immunized against Marek's disease by inoculation with viral antigens, but spleen cells from these immunized, bursectomized and irradiated donors did not confer protection on the recipients into which they were inje… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1982
1982
2000
2000

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…Adoptive cell-transfer techniques have been used successfully in mice to study the protective role of immune cells against many pathogens, including herpesviruses (Oakes, 1975;Rager-Zisman and Allison, 1976). In chickens the technique has been used to study the role of immune spleen cells (Powell et al, 1980) and nonimmune spleen cells Linna, 1979 and in resistance to the herpesvirus causing Marek's disease. Cell-transfer techniques have also been used to study the cells responsible for humoral immunity in chickens.…”
Section: Introductionmentioning
confidence: 99%
“…Adoptive cell-transfer techniques have been used successfully in mice to study the protective role of immune cells against many pathogens, including herpesviruses (Oakes, 1975;Rager-Zisman and Allison, 1976). In chickens the technique has been used to study the role of immune spleen cells (Powell et al, 1980) and nonimmune spleen cells Linna, 1979 and in resistance to the herpesvirus causing Marek's disease. Cell-transfer techniques have also been used to study the cells responsible for humoral immunity in chickens.…”
Section: Introductionmentioning
confidence: 99%
“…A delicate balance undoubtedly exists between the various lymphoid cell populations, and the complex immunological mechanisms which are involved in tumour inhibition and enhancement. The outcome of bursectomy or CY-treatment on lymphoid and other tumours of birds are, therefore, not unequivocal (Payne and Rennie, 1970;Linna etal., 1974;Calnek et al, 1978;Powell et al, 1980;Price and Smith, 1981). Data presented here showed that the humoral immune response of intact turkeys infected with LPDV was not decreased at 6 or 7 weeks post-infection.…”
Section: Discussionmentioning
confidence: 99%